Identity construction of Sami people with disabilities - Melbøe, Line (Western Sydney University, 2018)
Source at https://www.hca.westernsydney.edu.au/gmjau. The aim of this article is to explore how the political, technological and economic development of recent decades has influenced the identity construction of Sami people with disabilities. While Sami identity work is described as a continuous process carried out in everyday life, the subject is addressed through a presentation and discussion of three narratives. The analysis demonstrates how different types of development have expanded access for Samis with disabilities to participate in traditional Sami activities in many ways and, as such, have increased their opportunities to identify themselves as Sami. At the same time, however, changes in laws and regulations concerning ownership and use of land and sea resources seem to constitute political barriers that hinder disabled Samis from pursuing traditional Sami occupations and activities such as fishing and reindeer herding. Furthermore, ‘cultural blindness’ among professionals within the welfare system seems to block opportunities for Samis with disabilities to access their own culture through language and traditional Sami way of life. This lack of connection to traditional Sami activities is problematic as it may lead to the perception among both disabled Sami individuals and other Samis that these individuals are not entitled to define themselves as Sami.